Precise Distance Measurement for a Near-Earth Asteroid by the Refined Rotational Reflex Velocity Method - B. F. Guo; Q. Y. Peng; F. R. Lin; J. L. Cao (The Astronomical Journal, 2023)
The rotational reflex velocity (RRV) method was proposed by Heinze and Metchev in 2015 and was used to measure the distances of main-belt asteroids (MBAs). Later, Lin et al. generalized this method using spherical astronomy in 2016. The method measures the distances of MBAs using the observations from a single ground-based telescope over two nights. We refined this method and extend it further to the distance measurement of near-Earth asteroids (NEAs). In practice, we measure the distance of the potentially hazardous asteroid (99942) Apophis from the acquired CCD frames using the newly refined method. According to the requirement of the newly refined method, we also simulate the distance measurements of the four typical NEAs, (1221) Amor, (1862) Apollo, (2062) Aten, and (163693) Atira, on their discovery dates and follow-up dates. The measurement results of Apophis based on the newly refined RRV method show that the mean relative errors for the independent exposure frames on the successive two nights is ∼0.08% (about a factor of 2 improvement in comparison with the research of Lin et al.) compared with the distance from JPL ephemeris. Our simulation results also show that this refined method can accurately and precisely measure the distances of newly discovered NEAs in an astrometric way without performing orbital determination. The accurate and precise distances of newly discovered asteroids help us to conveniently evaluate their impact risks within a shorter time, leaving us more time to take defense precautions.